Micronucleus frequency of the buccal epithelial cells on pesticide-exposed female farmers in Dieng village, Central Java - Yudasari, Innayati Oktiana; Susilowati, Heni; Jonarta, Alma Linggar (The Indonesian Journal of Dental Research)
Pesticide is a toxic material used to eradicate physical intruder of crop, including pests, diseases, or weeds. Long-term exposure of pesticide to human body may give genotoxic effects at cellular level, as its substances are chemically bond with the components of DNA triggering the damage of DNA and chromosomes. Micronucleus, additional nucleus on the cells, presents as a result of the termination of the chemical bonds of DNA. The aim of this study was to investigate the frequency of micronuclei of buccal epithelial cells on pesticide-exposed female farmers in Dieng Village, Central Java. This research was conducted on 36 female villagers of Dieng Plateau. The first group consisted of 18 subjects who had regularly and directly exposed by pesticides due to their job as farmers. The control group consisted of 18 subjects were unexposed to pesticides. Buccal epithelium cells of all subjects was collected by swabing the right and left buccal mucosa using cytobrush, fixed and stained using Feulgen-Rossenbeck method. The micronuclei frequency was counted per 1000 epithelial cells. Data was analyzed using Independent Sample t-test. The statistical analysis showed a significant difference between exposed and unexposed groups (p= 0,01). It is concluded that there was an increase in the micronucleus frequency of buccal epithelial cells on pesticide-exposed female farmers in Dieng Village. Moreover, direct long-term exposure of pesticides may harm and damage the human body cells at the gene level.